Catholicism and the Supreme Court Reorganization Proposal of 1937 - Kenneally, James J. (A journal of church and state, 1983)
James J. Kenneally, B.S., Ph.D., M.Ed.; Catholicism and the Supreme Court Reorganization Proposal of 1937, Journal of Church and State, Volume 25, Issue 3, 1 Oc